Tingles down the spinal cord: A spinal functional magnetic resonance imaging investigation of the autonomous sensory meridian response. (July 2022) - Smith, Stephen D.; Kolesar, Tiffany A.; Fredborg, Beverley K.; Kornelsen, Jennifer
Autonomous sensory meridian response (ASMR) is a perceptual and emotional phenomenon in which specific sensory stimuli elicit a feeling of calm as well as tingling sensations on the scalp, neck, and shoulders. In the current study, we use fMRI to examine whether the motoric and sensory regions of the spinal cord segments associated with these body parts show increased activity during ASMR experiences. Nine individuals with ASMR completed six spinal functional magnetic resonance imaging runs while passively viewing videos. Three of the videos were shown (through pre-testing) to elicit ASMR tingles and three videos did not (i.e., control videos). The results demonstrated that ASMR-related stimuli elicited activity in dorsal (sensory) regions of spinal cord segments C1, C5, and C6; activity was observed in ventral (motoric) regions of segments C2–C8. Similar activity was not detected in response to control videos.